ANALISIS PENENTUAN SEKTOR EKONOMI UNGGULAN DI KABUPATEN SERAM BAGIAN BARAT (Analysis of the Determination of the Leading Economic Sector in West Seram Regency) - Valiant G. Marlessy; Rine Kaunang; Charles R. Ngangi (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The aim of this study was to analyze the economic sectors that can be prioritized in economic growth of the West Seram Regency. This research was carried out in West Seram Regency from March to August 2019. This study used secondary data obtained from the Central Statistics Agency of West Seram Regency and Maluku Province and the Regional Development Planning Board of the West Seram District. Data were analyzed using Location Quatien (LQ) and Dynamic Location Quotient (DLQ) analysis. The results showed that there were six leading sectors in West Seram District, namely: (1) agriculture, forestry and fisheries, (2) manufacturing, (3) construction, (4) real estate, (5) health services and social activities and (6) other service sectors. Based on the value of DLQ, the leading sector at the moment would be expected to remain ahead in the future. It is therefore recommended that these leading sectors remain prioritized in the regional development strategy without ignoring the non-leading sectors, so that all sectors are expected to be able to support each other in increasing the potential for economic growth of the West Seram Regency.Keywords: Leading Economic Sector, Economic Growth, West Seram